A shift-share analysis of electrical and electronic products: an overview and assessment of export growth of Malaysia - Al-Mamun, Abdullah; Rahman, Muhammad Khalilur; Taufiq, Muhamed; ., Muzammir (Canadian Center of Science and Education, 2015)
The study examines the global export market and its prospect for Malaysia’s electrical and electronic (E&E) products. The shift share technique is applied to identify the potential export growth by selected top fifteen countries for the period of 2006-2008 and 2009-2011. The findings of shift-share analysis indicate that the overall market has increased in export value as the market experienced has increased in each country except Japan, Thailand and USA. In addition, the results also reveal that Singapore has the highest growth rate and Cambodia has a comparatively lower rate. This paper discussed about the theoretical implications, conclusion and recommended for future study.